Effectiveness of ginger in reducing metabolic levels in people with diabetes: a randomized clinical trial (Revista Latino-Americana de Enfermagem, 2020)
Objective: to evaluate the effectiveness of ginge (Zingiber officinale) in reducing blood sugar and lipid levels in people with type 2 diabetes. Method: a randomized and double-blind clinical trial conducted with people with type 2 diabetes in primary care facilities. The study included individuals aged between 20 and 80 years old, using oral antidiabetic drugs and with HbA1c levels between 6.0% and 10%. The participants were paired 1:1, allocated in two distinct groups, and randomized in blocks, based on their HbA1c levels. In the experimental group, the participants used 1.2g of ginger and, in the control group, 1.2g of placebo, daily for 90 days. The primary outcome was a reduction in fasting blood sugar and HbA1c, and the secondary outcome was a reduction in lipids and HOMA-IR. 103 individuals completed the study, 47 in the experimental group and 56 in the control group. Results: the participants in the experimental group showed a greater reduction in the blood glucose and total cholesterol values compared to the control group. Conclusion: the use of ginger can help in the treatment of people with diabetes, and data support the inclusion of this herbal drug in the clinical practice of nurses. RBR-2rt2wy